A Survey on the Criteria for Measuring the Profitability of a Construction Organization - Memon, A. H.; Soomro, M. A.; Lakho, N. A.; Bhutto, M. A.; Memon, A. N. (Engineering, Technology & Applied Science Research, 2018)
Any organization’s performance depends on profitability which depends on several adopted criteria. The preference and level of adoption of these criteria varies, on different industries. This study focuses on investigating the criteria of profitability in the construction industry. This investigation involves a survey to seek the perception of the contractors involved in handling physical activities of construction works. The survey considered 63 questionnaire forms. Statistical analysis was performed to compute the frequency and the relative importance index. The results indicated that structural capital, lifetime values, capital structure and competitor actions are the top 4 criteria implemented in construction organizations to measure profitability.